Studi In Silico Senyawa Bahan Alam Terhadap Biomarker Pembelahan Sel Kanker - Iksen, Iksen; Sari, Hesti Yola (Herbal Medicine Journal, 2025)
Uncontrolled cancer cell division causes a high risk of death for cancer patients. One of the proteins that control cell division is CDK 4 and CDK6. The use of natural compounds as supporting therapy can reduce the toxicity symptoms of conventional chemotherapy. This study aimed to analyze the possible interactions of natural compounds such as allicin, alpha-mangoestin, curcumin and hesperetin on cancer cell division biomarkers (CDK4 and CDK6). This research process was carried out in silico using the Pyrx 0.8 program and Discovery Studio 2022. The parameters tested included binding energy, number of interactions and types of interaction. The results found that allicin, alpha-mangoestin, curcumin and hesperetin can interact with CDK4 and CDK6. The types of interactions formed between the ligand and the target protein are hydrogen bonds, hydrophobic bonds, and electrostatic bonds. In this study, it can be concluded that natural compounds such as allicin, alpha-mangoestin, curcumin and hesperetin are able to interact with CDK4 and CDK6 proteins in silico so that they are considered potential candidates for cancer drugs